GRITS Toolbox—a freely available software for processing, annotating and archiving glycomics mass spectrometry data. (23rd April 2019) - Weatherly, D Brent; Arpinar, F Sena; Porterfield, Melody; Tiemeyer, Michael; York, William S; Ranzinger, Rene
Abstract: Mass spectrometry (MS) is one of the most effective techniques for high-throughput, high-resolution characterization of glycan structures. Although many software applications have been developed over the last decades for the interpretation of MS data of glycan structures, only a few are capable of dealing with the large data sets produced by glycomics analysis. Furthermore, these applications utilize databases that can lead to redundant glycan annotations and do not support post-processing of the data within the software or by third party applications. To address the needs, we present GRITS Toolbox, a freely-available, platform-independent software application capable of storing and processing glycomics MS data along with associated metadata. GRITS Toolbox automatically annotates MS data using an integrated glycan identification module that references manually curated databases of mammalian glycans (provided with the software) or any user-defined databases. Extensive display routines are provided to post-process the data and refine the automated annotation using expert knowledge of the user. The software also allows side by side comparison of annotations from different MS runs or samples and exporting of annotations into Excel format.